Gamification Design to Build Engagement in Accounting Master Students University of Surabaya - Ikhwanul Arga Dentya Faresqi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to provide a new way to increase student motivation in participating in the lecture process. The current condition is that students feel tired due to lecture activities which feel like they are just routinely doing assignments after a day of work. Therefore, the researchers tried to apply the gamification concept design to present fresh and fun lecture activities without compromising the essence of the lecture process. The goal is that students are able to enjoy the lecture process without being burdened so that they can bring out their true potential.